Genetic diversity of Portuguese Arbutus unedo L. populations using leaf traits and molecular markers: an approach for conservation purposes - Lopes, Lucas Pereira (2014)
The genetic diversity within and between four natural Arbutus unedo L. populations in Portugal was investigated using morphological characters, inter-simple sequence repeats (ISSR) and random amplified polymorphic (RAPD) markers, for a proper conservation of this resource. The results showed a high morphological variation between and within-populations. The dry-weight, length, width and peduncle length of the leaves were the most discriminating characters, being responsible for 52.6% of the total variation. The molecular analysis, based on both RAPD and ISSR, indicated moderate genetic diversity within populations, with values of Nei’s gene diversity ranging from 0.16 to 0.39 and the Shannon’s diversity from 0.24 to 0.57. The highest genetic diversity occurred within Braganc¸ a population. At the species level, the genetic variation was mainly within populations (75%), suggesting a low-moderate genetic differentiation among populations. The high level of gene flow estimated among populations (1.499) showed to be the main reason for their low differentiation. The cluster analysis showed that only one population formed a distinctive cluster. The remaining formed a second cluster due to their geographical approach, which has been showed to affect significantly the genetic distances among populations. No correlation between RAPD and ISSR markers, and between the molecular and morphological data was found. From the conservation point of view it is proposed to combine both in- and ex situ approaches. The maintenance of sufficient gene flow and the increase of the effective population sizes are the main in situ actions proposed. The ex situ conservation, should involve the collection of a high number of individuals within populations.